2022
DOI: 10.33225/pec/22.80.531
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Collaborative Research Practices in Academia: Factors, Challenges, and Strategies

Abstract: This mixed-method research sought to identify the factors, challenges and strategies that enable and strengthen collaborative research practice in academia. Participants of the study are purposively chosen, self-selected faculty and students from an external campus and a unit in the main campus of a state university in Bulacan, Philippines, who have successfully completed collaborative research writing projects, presented collaborative research projects in conferences and symposia, or published said collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…With the social and interactive nature of SOL, student inquiries and concerns are directly and immediately addressed, and engagement with lesson contents and learning materials is done in real time (Hrastinski, 2008). Although there is limited literature on online research learning practices and pedagogy, it is highly valued and necessary in upgrading the research capacity of higher education institutions (Durante, 2022). Moreover, in an online research learning environment, literature has shown that learners become more flexible and are able to overcome logistic and physical barriers so that they can participate in research collaborations anytime and anywhere (Collins et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the social and interactive nature of SOL, student inquiries and concerns are directly and immediately addressed, and engagement with lesson contents and learning materials is done in real time (Hrastinski, 2008). Although there is limited literature on online research learning practices and pedagogy, it is highly valued and necessary in upgrading the research capacity of higher education institutions (Durante, 2022). Moreover, in an online research learning environment, literature has shown that learners become more flexible and are able to overcome logistic and physical barriers so that they can participate in research collaborations anytime and anywhere (Collins et.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2022;Chin 2020). Factors that contribute to the effectiveness of online collaborative research learning experience include: (1) recognizing the diversity of values, experiences, and personalities of collaborators, (2) assigning roles of members of the collaboration team, (3) how the members build relationships and their interdependence with each other, (4) how ergonomic, flexible, and adaptable the processes used by the groups are, (5) how the members of the group learn knowledge, skills, and expertise, and ( 6) what motivates the members of the research team (Durante, 2022).…”
Section: Introductionmentioning
confidence: 99%